2017
DOI: 10.3390/w9050337
|View full text |Cite
|
Sign up to set email alerts
|

The Winter Environmental Continuum of Two Watersheds

Abstract: This paper examines the winter ecosystemic behavior of two distinct watersheds. In cold-temperate regions, the hydrological signal and environmental parameters can fluctuate dramatically over short periods of time, causing major impacts to aquatic habitats. This paper presents the results of the 2011-2012 winter field campaign in streams and rivers near Quebec City, QC, Canada. The objective was to quantify water quantity and quality parameters and their environmental connectivity from headwater creeks above t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(24 citation statements)
references
References 41 publications
0
24
0
Order By: Relevance
“…In addition, ice cover has been also observed to reduce turbidities when compared to the open‐channel conditions of equivalent discharges (Kämäri et al, , ). However, Turcotte and Morse () have observed both lower or higher turbidities in ice‐covered channels than in open‐channel conditions. While the spring snow‐melt flood and ice breakup periods may be major sediment transport events and may also be when the greatest annual turbidities occur (Turcotte et al, ; Turcotte and Morse, ), the other seasons (including mid‐winter, where there are ice‐covered low flows) may cause great total channel changes (Lotsari et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, ice cover has been also observed to reduce turbidities when compared to the open‐channel conditions of equivalent discharges (Kämäri et al, , ). However, Turcotte and Morse () have observed both lower or higher turbidities in ice‐covered channels than in open‐channel conditions. While the spring snow‐melt flood and ice breakup periods may be major sediment transport events and may also be when the greatest annual turbidities occur (Turcotte et al, ; Turcotte and Morse, ), the other seasons (including mid‐winter, where there are ice‐covered low flows) may cause great total channel changes (Lotsari et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…However, Turcotte and Morse () have observed both lower or higher turbidities in ice‐covered channels than in open‐channel conditions. While the spring snow‐melt flood and ice breakup periods may be major sediment transport events and may also be when the greatest annual turbidities occur (Turcotte et al, ; Turcotte and Morse, ), the other seasons (including mid‐winter, where there are ice‐covered low flows) may cause great total channel changes (Lotsari et al, ). In subarctic sand‐/gravel‐bed rivers, earlier studies have shown the whole open‐channel low flow period (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Climate change effects must be viewed through a regional lens, understanding the specific types of changes in precipitation, temperature, wind, and other variables that may occur, and building an understanding of how that will affect the ecosystems in a region. To help build the necessary local-regional-global understanding, synthetic work to understand differences across watersheds, across lakes, across rivers, and across regions such as those already presented here [32,62,64] and elsewhere [3,9] is very valuable-identifying common responses of ecosystems through winter, and differences across regions, and across types of lakes and rivers. This type of comparative approach will help to build a more diverse, regionally-informed understanding of physical, hydrological, hydraulic, biogeochemical, and ecological change, particularly when coupled with work to inform process-based understanding of changes through winter (e.g., [10,12]), and to integrate our growing understanding of winter changes into model-based frameworks (e.g., [76][77][78]).…”
Section: Discussionmentioning
confidence: 99%
“…Winter changes span many more variables. Turcotte and Morse [64] studied the impact of ice breakup on peaks in specific conductivity and turbidity using a conceptual model, the winter environment continuum, to help relate the winter conditions in headwater streams to the water quality state along the river network during the winter. This linking of physical and chemical change is a key area for additional work across lentic and lotic environments.…”
Section: Water Qualitymentioning
confidence: 99%
“…rivers differ substantially from that of large rivers and the way ice forms is highly dependent on channel gradient, channel morphology, and weather characteristics such as the amount and type of precipitation (Buffin-Bélanger et al, 2013;Turcotte & Morse, 2013;Turcotte et al, 2012). In general, smaller rivers tend to have a wider range of ice types than large rivers (e.g., anchor ice-Figure 1c, suspended ice cover and ice shells-Figure 1e, solid ice coverage, floating ice), due to variation in channel morphology (e.g., presence of woody debris dams) and degree of warming from groundwater (Turcotte & Morse, 2017;Turcotte et al, 2014a).…”
Section: Ice Types and Formationmentioning
confidence: 99%